Postnatal growth of Infants with neonatal diabetes: insulin pump (CSII) versus Multiple Daily Injection (MDI) therapy - Alyafie, Fawzia; Soliman, Ashraf T; Sabt, Aml; Elawwa, Ahmed; Alkhalaf, Fawzia; Alzyoud, Mahmoud; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2019)
Background: Permanent neonatal diabetes mellitus (PNDM) is characterized by the onset of hyperglycemia within the first six months of life. Their diabetes is associated with partial or complete insulin deficiency with variable degree of intrauterine growth retardation. Insulin therapy corrects the hyperglycemia and results in improvement of growth. However, no studies have reported the longitudinal growth of these infants (head circumference, length and weight gain) after starting insulin therapy. Patients and methods: We assessed the growth parameters weight (Wt), Length (L) and head circumference (HC) in 9 infants with PNDM, during the first 2 years of their postnatal life. Five infants were on insulin pump therapy (CSII) and 4 were on multiple doses of insulin injection (MDI) therapy. Results: On insulin therapy for 20±4 months catch-up growth occurred in the majority of infants. L-SDS increased from -1.45 to -0.65 , HC-SDS from -2.3 to - 0.51 and Wt-SDS increased from -1.94 to - 0.7 at the end of the 20±4 months of age, after starting insulin therapy. Two out of 9 infants had a L-SDS